Pharmacological blocking of the osteoclastic biocorrosion of surgical stainless steel in vitro1. Issue 4 (10th September 2012) - Lionetto, S.; Little, A.; Moriceau, G.; Heymann, D.; Decurtins, M.; Plecko, M.; Filgueira, L.; Cadosch, D.
Abstract: In vitro studies suggest that human osteoclasts (OC) are able to corrode surgical stainless steel 316L (SS). The aim of this study was to investigate whether osteoclastic biocorrosion can be blocked pharmacologically. Human OCs were generated in vitro from peripheral blood monocytic cells (PBMCs) in the presence of OC differentiation cytokines. The osteoclastic viability, differentiation, and resorptive function (on both bone and SS) were assessed using standard colorimetric cell viability assay 3‐(4, 5‐dimethylthiazol‐2‐yl)‐5‐(3‐carboxymethoxyphenyl)‐2‐(4‐sulfophenil)‐2H‐tetrazolium, inner salt (MTS), fluorescence microscopy, tartrate‐resistant acid phosphatase expression (flow cytometry), and scanning electron microscopy. OCs cultured on SS were exposed to nontoxic concentrations of bafilomycin A1, amiloride hydrochloride, or zoledronic acid. The extent of biocorrosion was quantified using atomic emission spectrometry (to measure the concentration of metal ions released into the supernatant) and scanning electron microscopy. PBMCs differentiated into mature and functional OC in the presence of all the drugs used. Osteoclastic resorption of SS was noted with differences in the resorption pattern for all drug treatments. Under the drug treatments, single areas of osteoclastic resorption were larger in size but less abundant when compared with positive controls. None of the drugs used were able to inhibit osteoclastic biocorrosion of SS. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A, 2013.